Ramona and Beezus - Craig, Laurie; Pustay, Nick.; Di Novi, Denise; Greenspan, Alison; Allen, Elizabeth, 1971-; Moynahan, Bridget, 1972-; Goodwin, Ginnifer; King, Joey.; Duhamel, Josh, 1972-; Oh, Sandra, 1971-; Corbett, John, 1961-; Gomez, Selena, 1992-; et al. (Beverly Hills, Calif. : 20th Century Fox, 2010)
Ramona is a little girl with an imagination and a nose for mischief. Her playful antics keep everyone in her loving family on their toes, including her older sister Beezus, who's just trying to survive her first year of high school. Through all the ups and downs of childhood, Ramona and Beezus learn that anything's possible when you believe in yourself and rely on each other. Based on the best- selling books by Beverly Cleary.
Based on Beverly Cleary's novel, Beezus and Ramona.
Directory of photography, John Bailey ; editor, Jane Moran ; music by Mark Mothersbaugh.
Bridget Moynahan, Ginnifer Goodwin, Joey King, Josh Duhamel, Sandra Oh, John Corbett, Selena Gomez.
MPAA rating: G.
DVD; widescreen; 5.1 Dolby digital; Dolby surround.
English or French dialogue; English or Spanish subtitles; closed-captioned.
Keywords: Quimby, Ramona (Fictitious character) -- Juvenile drama; Self-confidence -- Juvenile drama; Families -- Juvenile drama; Feature films; Children's films; Films for the hearing impaired